Enterohaemorrhagic E.coli O157 in locally produced soft cheese - Al-Khyat, Fadia Abd AL-Muhsin (The Iraqi Journal of Veterinary Medicine, 2008)
Escherichia coli is consedered to be one of the normal flora of the humanand animal intestinal tract, but there are some serotypes which are diagnosedas a pathogenic such as Enteroheamorrhagic E.coli O157 that cause diseaseranging in severity from mild to lethal and it’s significant as a major foodbornepathogen and as a public health problem. The purpose of this studywas to provide the prevalence of E.coli and E.coli O157 in locally producedsoft cheeses, detection and enumeration were carried out using specificdifferential media (CT.SMAC,E.M.B.), serological test (Latex O157) andbiochemical test.A total of 50 samples of locally produced soft cheeses were collected fromsupermarket in Baghdad City during the period from April till the end ofMay 2007. The result revealed that there was a significant (P<0.05)difference in the isolation percentage, E.coli was isolated from 47 samples(94%) while E.coli O157 isolated from 40 samples (80%). The data alsorevealed that there was a significant (P<0.05) difference in the mean ofmicrobial counts E.coli and E.coli O157 recorded (4.7x106 , 2.4x105CFU/g) respectively. These result suggest that the serotype O157 isprevalent within dairy product and processing environment.